2017
DOI: 10.1002/cncr.30862
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and the chronic cancer patient: Patterns in treatment‐related effects, follow‐up care, and use of survivorship care plans

Abstract: A substantial number of CC survivors, often considered incurable but treatable, seek survivorship support. Tools to facilitate participation, communication, and coordination of care are valuable for these patients, and future iterations of SCPs should be designed to address the particular circumstances of living with CC. Cancer 2017;123:4268-4276. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The papers included feasibility and evaluation studies of the SCP technology (16)(17)(18), descriptive studies using SCP data and/or surveys/questionnaires on user satisfaction and participation (19)(20)(21)(22)(23)(24)(25)(26), predictive modelling as to who receives a SCP (27), a review on the adherence, advantages and limitations of cancer SCP (28), a review with a focus on nursing practice(29) and a description of SCP systems that were under development at the time (30,31).…”
Section: Insert Figure 1: Prisma Search Flowchart About Herementioning
confidence: 99%
See 2 more Smart Citations
“…The papers included feasibility and evaluation studies of the SCP technology (16)(17)(18), descriptive studies using SCP data and/or surveys/questionnaires on user satisfaction and participation (19)(20)(21)(22)(23)(24)(25)(26), predictive modelling as to who receives a SCP (27), a review on the adherence, advantages and limitations of cancer SCP (28), a review with a focus on nursing practice(29) and a description of SCP systems that were under development at the time (30,31).…”
Section: Insert Figure 1: Prisma Search Flowchart About Herementioning
confidence: 99%
“…Most survivors using one model planned to share it with their PCPs (17,19,(22)(23)(24)(25). Reasons for not sharing the care plan were that their provider would not care about the plan, they did not feel the plan was relevant to the provider or that the SCP was too long or it would upset the provider (23,25).…”
Section: Insert Figure 1: Prisma Search Flowchart About Herementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Some evidence suggests that provider communication, follow-up care, and health outcomes may improve when survivors and followup care providers receive survivorship care plans (SCPs), written documents containing information regarding cancer diagnosis, treatment, surveillance plans, and health promotion. 5,6 Eight randomized controlled trials of SCPs have found no effect on service or patient outcomes [7][8][9][10][11][12][13][14][15][16][17][18][19][20] ; however, observational studies have found that SCPs improve survivors' psychological well-being, 21 self-efficacy and self-reported health, 18 confidence in survivorship information and care, understanding about cancer, treatment, and follow-up care, 22-24 peace of mind, 25 and cancer screening rates. 26 Evidence also suggests that SCPs improve follow-up care providers' confidence in caring for survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the directive by the Institute of Medicine 12 years ago highlighted the weaknesses in the management of cancer survivors and strongly recommended the implementation of treatment summaries and survivorship care plans (SCPs) as a means to improve the coordination of care, SCPs have garnered increasing support in the field of medical oncology . Despite this trend with our colleagues, radiation oncologists have been slower to adopt this paradigm . According to the data presented in the accompanying article by Frick et al, only 18% (95% confidence interval, 10%‐29%) of radiation oncologists are providing detailed SCPs to their patients and only 24% (95% confidence interval, 15%‐35%) provide SCPs as part of standard communication with a patient's primary care provider.…”
mentioning
confidence: 99%